Peran Manajemen Sumber Daya Manusia dalam Era Globalisasi: (Kajian Studi Literatur) - Dahlan Somantri; Suradi Suradi; Hidayat Hidayat; Sri Mulyeni (Global Leadership Organizational Research in Management, 2025)
This study highlights the paradigmatic shift in human resource management (HRM) in response to the complexities of globalization. Globalization has not only expanded the geographical scope of business but also reconfigured demands for competencies, technology, and cultural dynamics within organizations. Using the systematic literature review (SLR) method, this article examines adaptive HRM strategies focused on three pillars: (1) developing global competencies through cross-cultural training and digital literacy, (2) integrating technologies such as artificial intelligence (AI) in recruitment and performance evaluation, and (3) managing cultural diversity to create an inclusive work ecosystem. Analytical findings reveal that organizations with holistic HRM approaches combining strategic agility, investment in employee upskilling, and data-driven systems tend to excel in mitigating risks of global market disruptions. Critical insights emphasize that success relies not only on technology adoption but also on managerial capabilities to address cultural conflicts and facilitate cross-border collaboration. The research concludes that strategic HRM serves as a driver of organizational innovation and sustainability, with practical recommendations for companies to develop evidence-based HRM frameworks aligned with global trends.